PENGARUH KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA DI PERUSAHAAN CV. ASSALAM FAMILLY - Indri Aprianti; Raisa Hilia Aini Syifa (JURNAL EKONOMI PERJUANGAN, 2026)
An organization's ultimate triumphs are fundamentally anchored in the quality of its human capital. Consequently, fostering employee job satisfaction becomes an imperative mandate for management, given its direct bearing on staff morale, organizational loyalty, operational discipline, and overall output. Driven by this premise, the present inquiry utilized a quantitative methodology framed within an associative framework to gauge how remuneration packages and internal motivation impact worker satisfaction at CV Assalam Family. By adopting a saturated sampling strategy, the entire workforce of the enterprise was mobilized as active research participants. Primary data was gathered via Likert-scale questionnaires, which were subsequently subjected to multiple linear regression modeling using IBM SPSS Statistics software.Empirical evidence from the statistical analysis indicates that financial compensation exerts a positive and highly meaningful influence on workforce satisfaction, evidenced by a regression coefficient of 0.464 and a significance value of 0.000, which falls safely below the 0.05 threshold. Parallel to this finding, drive and motivation were also shown to yields a positive, statistically reliable boost to job satisfaction, returning a coefficient value of 0.325 and a significance metric of 0.001 (less than 0.05). Furthermore, when tested simultaneously, the joint interplay of motivation and salary demonstrates a powerful collective impact on overall employee contentment, as validated by an F-statistic of 41.855 and an overall significance rating of 0.000. Ultimately, the coefficient of determination reveals that 41.7% of the variance in employee job satisfaction within this firm can be explicitly accounted for by these two combined determinants.